POLA PEMBELAJARAN MATEMATIKA DALAM MENINGKATKAN PRESTASI OLIMPIADE SAINS DI MADRASAH ALIYAH DARUL MURSYID - Lase, Arjun Arifin (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
This research uses methodological tools with a descriptive qualitative approach based on the phenomenological paradigm through supporting instruments (interviews, observations, documentation) which allows objective data to be brought to the surface. The results of this research show that: (1) The pattern of organizing mathematics learning carried out at Madrasah Aliyah Darul Mursyid is by establishing a clear and measurable curriculum that is formed together with all education stakeholders in the madrasah environment. (2) The pattern of delivery of mathematics learning carried out at Madrasah Aliyah Darul Mursyid. First; Darul Mursyid highly upholds the principles of creativity and effectiveness in student learning. Second; Learning media is directed to use more varied and innovative models. Third; Learning in KBM classes or Olympiads must use interactive and dynamic learning methods. (3) The management pattern for mathematics learning carried out at Madrasah Aliyah Darul Mursyid is prepared jointly by all madrasah and Islamic boarding school stakeholders. Starting from preparing the curriculum structure to assigning teachers to fields of study and determining study hours for a particular curriculum content. Requires teachers to keep journals and records of student progress in their field of study and evaluate them periodically by the madrasah. (4) The results of applying mathematics learning patterns in improving science olympiad achievements at Madrasah Aliyah Darul Mursyid show that the achievements achieved by students in various science olympiad events have succeeded in winning champions each year, especially overall champions. Keywords: Learning Patterns, Learning Mathematics, Science Olympiad Achievement